Investigations of the natTi(p,x)43,44m,44g,46,47,48Sc,48V nuclear processes up to 40 MeV - Khandaker, Mayeen Uddin; Kim, K.; Lee, M.W.; Kim, K.S.; Kim, G.N.; Cho, Y.S.; Lee, Y.O. (Elsevier, 2009)
Independent and cumulative production cross-sections for the Ti-nat(p,x)V-48, Sc-43,Sc-44m,Sc-449,Sc-46,Sc-47,Sc-48 nuclear processes are reported here, for the energy region of 4-38 MeV by using a stacked-foil activation technique. Measured data were critically compared with the earlier reported values, and also with the theoretical data from the TALYS and ALICE-IPPE codes. The measured Ti-nat(p,x)48V reaction is important for charged particle beam monitoring purposes, whereas the Sc-43,Sc-44,Sc-47 radionuclide have various practical applications in nuclear medicine. (C) 2009 Elsevier Ltd. All rights reserved.